2020
DOI: 10.1016/j.rmed.2020.106188
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of therapeutic plasma exchange in the treatment of penn class 3 and 4 cytokine release syndrome complicating COVID-19

Abstract: Objectives Cytokine release syndrome (CRS) is a potentially severe complication of COVID-19 most commonly resulting in respiratory failure. This ten-patient study was designed to determine the efficacy of therapeutic plasma exchange (TPE) in improving oxygenation and in reducing the cytokine load in a critically ill subset of patients. Methods Five single volume plasma exchanges over eight days within a 14-day study period. In mechanically ventilated patients, oxygenati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
81
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(88 citation statements)
references
References 29 publications
6
81
0
Order By: Relevance
“…After excluding some of the articles for numerous reasons, the final 18 papers were included in the systematic review. The most common types of studies were case-series studies ( n = 14) [ 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 ], then case-control studies ( n = 2) [ 17 , 35 ] and a propensity score matched study [ 36 ]. Only one randomized controlled trial was included in the analysis [ 37 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After excluding some of the articles for numerous reasons, the final 18 papers were included in the systematic review. The most common types of studies were case-series studies ( n = 14) [ 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 ], then case-control studies ( n = 2) [ 17 , 35 ] and a propensity score matched study [ 36 ]. Only one randomized controlled trial was included in the analysis [ 37 ].…”
Section: Resultsmentioning
confidence: 99%
“…Out of 384 patients, 220 received TPE. The number of patients in the studies varied from 3 to 90 with a median of 8 patients (IQR 5–18) [ 17 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 ]. The mean or the median age of participants in seven studies was below 65 years [ 8 , 10 , 11 , 12 , 13 , 14 , 15 ], whereas in the remaining four studies, it was above 65 years [ 5 , 6 , 7 , 9 ].…”
Section: Resultsmentioning
confidence: 99%
“…Finally, the precise timing of such treatment, if effective, remains to be determined. Indeed, in addition to removing auto-Abs against type I IFNs, PE in COVID-19 patients could theoretically act on various targets, thereby affecting coagulation [ 18 ], inflammatory mediators [ 6 , 7 ], or antiviral innate immunity, as described here. The timing of PE may, therefore, be crucial: for the removal of auto-Abs against type I IFNs and the restoration of type I IFN antiviral immunity, treatment should probably be performed earlier in the course of the disease, when the virus is still in the early phases of replication, viral load is highest, and the patients have not yet become critically ill.…”
Section: Discussionmentioning
confidence: 99%
“…Liu et al reported that PE was used in 9 of 23 patients admitted to the ICU and a decrease in blood cytokines after PE [14]. Gluck et al performed five sessions of PE over 8 days in 10 patients with increased oxygen demand [15]. Ventilated patients also reported an average 78% improvement in PaO 2 /FiO 2 ratio, and significant decreases in blood levels of CRP and cytokines.…”
Section: Discussionmentioning
confidence: 99%